Hypoxia Induced Downregulation of Na+/H+ Exchanger-1 Activity Decreases Tumor Cell Proliferation - Gül Şimşek; Hilmi Burak Kandilci (Ankara Üniversitesi Tıp Fakültesi Mecmuas)
Objectives: Hypoxia and acidosis are the hallmarks of proliferative tumor microenvironment which can modulate the expression and function of Na+/H+ exchanger-1 (NHE1) via hypoxia inducible factor 1 (Hif). Here, we investigate the severity and time dependent effects of chronic hypoxia on NHE1 activity and its correlation with cell proliferation in mouse atrium tumor derived HL-1 cells. Materials and Methods: NHE1 activity was recorded using intracellular pH (pHi) sensitive dye cSNARF-1 (Leica SP5). Cell proliferation was assessed by live cell movie analyzer (Nanoentek, JuLI Br®) or immunofluorescence method. Results: According to our results, mild chronic hypoxia (2% O2, 48 hours) or shorter duration severe chronic hypoxia (1% O2, 24 hours) did not affect cell proliferation and NHE1 activity. In contrast, long term dimethyloxalylglycine (DMOG, Hif stabilizer) or zoniporide (NHE1 inhibitor) incubations (21% O2, 24/48 hours) suppressed cell proliferation. Conclusion: When our published and current results in this study interpreted together, at a critical level and duration of chronic hypoxia, Hif mediated downregulation of NHE1 activity could suppress tumor cell proliferation regardless of the well-known anti-proliferative early term direct effects of Hif. Therefore, restriction of NHE1 activity in tumor hypoxia is an important alternative target in regulating anti-proliferative action against tumor cells.